Conceptual Elements and Heuristics from Complexity Paradigm Suitable to the Study of Evapotranspiration at the Landscape Level - Coronel, Claudia; Silva, Omar Tapia; Hernández, Gilberto; Madrigal, José Manuel; Rosales, Edgar; Toledo, Alejandro; Galeana, Mauricio; Caloca, Alejandra López; Silvan, José Luis (IntechOpen, 2011)
None